BioClay nanosheets infused with GA3 ameliorate the combined stress of hexachlorobenzene and temperature extremes in Brassica alboglabra plants - Ahmad, Aqeel; Khan, Tanveer Alam; Shahzad, Sharoon; Ullah, Sami; Shahzadi, Iqra; Ali, Aamir; Akram, Waheed; Yasin, Nasim Ahmad; Yusuf, Mohammad (Frontiers in Plant Science, 2022)
Mitigation of stress caused by climatic change and environmental pollutants is a prime goal nowadays. Hexachlorobenzene (HCB) is an airborne and aero-disseminated POP molecule causing severe health issues in humans. Temperature extremes and HCB stress severely affect the growth and yield of subjected crop plants. The higher HCB uptake and accumulation by edible plants ultimately damage human health through the contaminated food chain. Hence, confining the passive absorbance of persistent organic pollutants (POPs) is a big challenge for researchers to keep the plant products safer for human consumption. BioClay functional layered double hydroxide is an effective tool for the stable delivery of acidic molecules at plant surfaces. The current study utilised gibberellic acid (GA3) impregnated BioClay (BioClayGA) to alleviate abiotic stress in Brassica alboglabra plants. Application of BioClayGA mitigated the deleterious effects of HCB besides extreme temperature stress in B. alboglabra plants. BioClayGA significantly restricted HCB uptake and accumulation in applied plants through increasing the avoidance efficacy (AE) up to 377.61%. Moreover, the exogenously applied GA3 and BioClayGA successfully improved the antioxidative system, physiochemical parameters and growth of stressed B. alboglabra plants. Consequently, the combined application of BioClay and GA3 can efficiently alleviate low-temperature stress, heat stress, and HCB toxicity.